Metal object and method of manufacturing same
By mixing the metal powder with the wax component and processing it during heating and cooling, the problem of uneven aluminum alloy coating in the prior art is solved, and a more uniform and stable alloy coating is achieved.
Patent Information
- Application Number
- JP2022519029
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-25
- Filing Date
- 2020-09-25
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2040-09-25
AI Technical Summary
Prior art When manufacturing metal objects, the aluminum alloy coating is uneven, resulting in thick coatings in some parts and thin coatings in some parts, affecting its performance in different applications.
By mixing the metal powder with the wax component, heat until the wax melts, then cools to room temperature, and then heat treatment is performed to form an alloy layer between the metal object and the metal powder.
This method significantly improves the uniformity of the alloy coating on the surface of metal objects, ensuring the stability and performance consistency of the coating in different application environments.
Smart Images

Figure 0007665604000001 
Figure 0007665604000002 
Figure 0007665604000003
Abstract
Description
[Technical field]
[0001] background The present invention relates to a method for producing a coated metal object, the coated metal object being obtained by applying a metal powder composition to the metal object, the coating comprising one or more wax components. The metal object is then heated to the melting temperature of the wax and cooled again to room temperature before being heat treated to form an alloy between a part of the metal object and the applied metal powder. The melting of the wax and the subsequent cooling allows to obtain a metal object with a more uniform alloy coating. The corresponding method is used in particular in sintering technology. The invention also relates to a method for subsequently treating the heat-treated metal object with a basic solution. The corresponding method is used in particular in the production of catalysts. The invention also relates to a metal object obtained by the method disclosed herein, which is used, for example, as a support and structural part and in catalytic technology.
[0002] prior art A method for producing a metal object coated with an alloy is known from the prior art, for example from WO2019057533. This method consists in applying a metal powder to a metal object and then heat treating the metal object, thereby forming an alloy in the contact area between the metal object and the metal powder.
[0003] One problem with this method is that it can result in non-uniform alloy coverage of the metal object, with some areas of the surface having high alloy coverage and other areas having low alloy coverage, which can lead to various drawbacks depending on the intended application. The reason for the non-uniform alloy coverage is not yet clear.
[0004] In view of the wide range of potential applications of alloy-coated metal objects, there is a need for methods of their manufacture that achieve more uniform alloy coatings on metal objects.
[0005] The present invention The present invention provides a corresponding method for achieving a more uniform alloy coating of a metal object. The method for producing a coated metal object according to the present invention comprises the steps of: (a) obtaining a coated metal object 1 by applying a metal powder composition to the metal object, the coating comprising one or more wax components; (b) heating the coated metal object 1 to the melting temperature of at least one of the wax components and then cooling to room temperature to obtain a coated metal object 2; (c) heat treating the coated metal object 2 to form an alloy between the metal portion of the metal object and the metal powder composition, thereby obtaining a metal object 3; where The metal object used in step (a) comprises a metal component selected from the group consisting of nickel, cobalt, copper, and iron; The metal powder composition used in step (a) comprises a powdered metal component comprising aluminium, silicon or magnesium, either in elemental or alloyed form.
[0006] In contrast to the prior art methods, in the method according to the invention the wax is first melted and then cooled again before alloying by heat treatment (see step (b)). Experimental results obtained in accordance with the present invention have shown that in order to achieve the desired more homogeneous alloy coating, it is actually necessary to melt and cool the wax as described in step (b) before alloying by heat treatment. It is not sufficient to simply add the wax to the metal powder and then apply the metal powder (step (a)) followed by alloying by heat treatment (step (c)).
[0007] In step (a) of the method 1 according to the invention, a coated metal object 1 is obtained by applying a metal powder composition to the metal object, the coating comprising one or more wax components.
[0008] The application of the metal powder composition in step (a) of the method according to the invention can be carried out in various ways, for example by bringing the metal body into contact with the metal powder composition by rolling or immersion, or by applying the metal powder composition by spraying, scattering or casting. For this purpose, the metal powder composition can be present as a suspension or in the form of a powder.
[0009] Preferably, the metal object is impregnated with a binder beforehand, prior to the actual application of the metal powder composition to the metal object in step (a) of the method according to the invention, for example, but not limited to, by spraying the binder or by immersing the metal object in the binder. The metal object thus prepared can then be applied with the metal powder composition.
[0010] Alternatively, the binder and the metal powder composition can be applied in one step. For this, the metal powder composition is suspended in the liquid binder itself before application, or the metal powder composition and the binder are suspended in the auxiliary liquid F.
[0011] The binder is a composition that can be completely converted into a gaseous substance by heat treatment in the temperature range of 100 to 400 ° C., and contains an organic compound that promotes adhesion of the metal powder composition to the metal object. Preferably, the organic compound is selected from the following group: polyethyleneimine (PEI), polyvinylpyrrolidone (PVP), ethylene glycol, mixtures of these compounds. PEI is particularly preferred. The molecular weight of polyvinylpyrrolidone is preferably in the range of 10,000 to 1,300,000 g / mol. The molecular weight of polyethyleneimine is preferably in the range of 10,000 to 1,300,000 g / mol. The molecular weight of polyethyleneimine (PEI) is particularly preferably in the range of 700,000 to 800,000 g / mol.
[0012] The auxiliary liquid F must be suitable for suspending the metal powder composition and the binder, and must be capable of being completely converted into a gaseous substance by heat treatment in the temperature range of 100 to 400° C. Preferably, the auxiliary liquid F is selected from the following group: water, ethylene glycol, PVP, and mixtures of these compounds. Usually, when an auxiliary liquid is used, the binder is suspended in water at a concentration in the range of 1 to 10% by weight, and then the metal powder composition is suspended in this suspension.
[0013] To obtain, at the end of step (a) of the method according to the invention, a coated metal object 1, whose coating comprises one or more wax components, one or more wax components must be added to the coating. For this purpose, the following approaches can be chosen, alone or in combination: (i) adding one or more wax components to the metal powder composition; (ii) adding one or more wax components to the binder; (iii) adding one or more wax components to the auxiliary liquid F; (iv) applying one or more wax components to an uncoated metal object; (v) applying one or more wax components to the binder-coated metal object; (vi) applying one or more wax components to the metal object 1 coated with the metal powder composition;
[0014] In a preferred embodiment of the present invention, one or more wax components are added to the metal powder composition (method (i)).
[0015] Waxes are substances defined by their mechanical and physical properties. Their chemical composition and origin can be very different. They differ from similar synthetic and natural substances (e.g. resins, plastic materials, metal soaps, etc.) mainly in that they change into a molten, liquid, low-viscosity state, generally at about 50-90 °C, but exceptionally up to about 250 °C, and are practically free of ash-forming compounds. Waxes are divided into three groups based on their origin, namely (i) natural waxes, which include vegetable waxes (e.g., candelilla wax, carnauba wax, wood wax, espartograss wax, cork crow, guaruma wax, rice germ oil wax, sugarcane wax, ouricle wax, montan wax, etc.), animal waxes (e.g., beeswax, shellac wax, spermaceti wax, lanolin or wool wax, uropygial grease, etc.), and mineral waxes (e.g., ceresin, ozokerite or earth wax, etc.); (ii) chemically modified waxes, which include hard waxes (e.g., montan ester wax, sasole wax, hydrogenated jojoba wax, etc.); and (iii) synthetic waxes, which include polyalkylene waxes, polyalkylene glycol waxes (e.g., polyethylene glycol waxes). The main components of renewable natural waxes are esters of long-chain fatty acids (wax acids) with long-chain fatty alcohols or with triterpene or steroid alcohols, and these wax esters also contain free carboxyl and / or hydroxyl groups. Natural fossil waxes, derived for example from lignite or petroleum, as well as Fischer-Tropsch waxes and polyalkylene waxes (e.g. polyethylene waxes), consist mainly of linear hydrocarbons, although branched and alicyclic hydrocarbons may also be present depending on the source. In many cases, these "hydrocarbon waxes" are functionalized by subsequent oxidation or, in the case of polyolefin waxes, by comonomers bearing carboxyl groups.For further details on the term wax, reference is made to Roempp Chemielexikon, 10. edition, vol. 6, 1999, Georg Thieme Verlag Stuttgart / New York, p. 4906, under the heading "Wachse", and the documents cited therein, in particular Cosm. Toil. 101, 49 (1986), as well as to DGF-Einheitsmethoden, Abteilung M-Wachse und Wachsprodukte, 7. Ergaenzungslieferung 05 / 1999, Stuttgart: Wissenschaftliche Verlagsgesellschaft, the aforementioned documents being incorporated herein by reference in their entirety.
[0016] A substance or substance mixture is referred to as a wax component within the meaning of the present invention if it is: (i) is a kneadable solid at 20°C; (ii) melts without decomposition at temperatures above 40°C; and (iii) It can be completely converted into a gaseous substance by pyrolysis in the temperature range of 100 to 400°C.
[0017] Hydrophobic wax components are preferred, ie surfaces composed of or coated with these substances or substance mixtures have a contact angle with water of greater than 90 degrees.
[0018] Preferably, all wax components have a solidification temperature in the range of 90 to 250°C.
[0019] Particularly preferred is a wax component having a solidification temperature of 45 to 160°C, particularly 100 to 160°C.
[0020] Particularly preferably, the wax component is stearamide wax (ethylene bis(stearamide), EBS).
[0021] The total amount of all wax components is selected such that its proportion relative to the total weight of the coating of the metal object 2 (obtained according to step (b) of the method according to the invention) is between 0.5 and 5% by weight. Preferably, the proportion of the total amount of all wax components relative to the total weight of the coating of the metal object 2 is between 1% and 4% by weight. The total weight of the coating of the metal object 2 corresponds to the difference in weight between the metal object 2 and the uncoated metal object used in step (a).
[0022] According to the invention, the metal object used in step (a) comprises a metal component selected from the group: nickel, cobalt, copper, iron.
[0023] In a preferred embodiment, the metal object used in step (a) consists of either: (i) Nickel metal (ii) Cobalt metal (iii) metallic copper; (iv) Nickel and cobalt alloys (v) Nickel and copper alloys (vi) An assembly of two overlapping layers of two separate metal components, where one of the metal components forms an inner layer of the metal object and the other of the metal components forms an outer layer of the metal object, the metal components being selected from the following list of combinations: nickel on the inside and cobalt on the outside, iron on the inside and nickel on the outside.
[0024] In a further preferred embodiment, the metal object used in step (a) consists of a metal selected from the group Ni, Fe, Co, Cu.
[0025] The metal objects used in step (a) of the method according to the invention can have any desired shape, for example cuboid, cuboid, cylinder, etc. However, they can also have the form of foams, nets, woven fabrics, loop-drawn knits or loop-formed knits, which may be shaped into monoliths. Preferably, the metal objects used in step (a) of the method according to the invention are in the form of foams, nets, woven fabrics, loop-drawn knits or warp knits.
[0026] In a particularly preferred embodiment of the method according to the invention, the metal object used in step (a) is a metal foam. In the context of the present invention, metal foam is understood to mean a foamed metal object, for example as disclosed in Ullmann's Encyclopedia of Industrial Chemistry, chapter "Metallic Foams", published online on 15 July 2012, DOI: 10.1002 / 14356007.c16_c01.pub2. In principle, metal foams with different morphological properties in terms of pore size and pore shape, layer thickness, areal density, geometric surface, porosity, etc. are suitable. Preferably, metal foams composed of Ni, Cu and / or Co have a density of 400 to 1500 g / m 2The foam has a density in the range of 0.5-10 mm, preferably 1.0-5.0 mm, a pore size of 400-3000 μm, preferably 400-800 μm, and a thickness in the range of 0.5-10 mm, preferably 1.0-5.0 mm. The production can be carried out by known methods. For example, the foam made of organic polymers can be coated with at least one first metal, after which the polymer can be removed, for example by pyrolysis or dissolution in a suitable solvent, whereby a metal foam is obtained. For coating with at least one first metal or its precursor, the foam made of organic polymers can be brought into contact with a solution or suspension containing the first metal. This can be carried out, for example, by spraying or immersion. Deposition by chemical vapor deposition (CVD) is also possible. For example, the polyurethane foam can be coated with the first metal, after which the polyurethane foam can be pyrolyzed. Polymer foams suitable for producing moulded bodies in the form of foams preferably have a pore size in the range of 100-5000 μm, particularly preferably 450-4000 μm, in particular 450-3000 μm. Suitable polymer foams preferably have a layer thickness of 5 to 60 mm, particularly preferably 10 to 30 mm. Suitable polymer foams preferably have a layer thickness of 300 to 1200 kg / m 3 The specific surface area is preferably 100 to 20,000 m 2 / m 3 , particularly preferably 1000 to 6000 m 2 / m 3 The porosity is preferably in the range of 0.50 to 0.95.
[0027] The metal powder composition used in step (a) of the method according to the invention may contain, in addition to one or more powdered metal components, one or more wax components and / or additives which contribute to improving flowability or water resistance. Such additives must be completely convertible into gaseous matter by heat treatment in the temperature range of 100-400° C. The metal powder composition used in step (a) of the method according to the invention comprises one or more powdered metal components selected from the following group: aluminum, aluminum alloys, silicon, silicon alloys, magnesium, magnesium alloys. In a preferred embodiment, the metal powder composition used in step (a) comprises one or more powdered metal components selected from the group consisting of aluminum, silicon, magnesium, an alloy of aluminum and chromium, an alloy of aluminum and molybdenum, an alloy of aluminum and copper, an alloy of aluminum and iron, an alloy of aluminum and iron and chromium, an alloy of aluminum and titanium, an alloy of aluminum and molybdenum and titanium, an alloy of silicon and chromium, an alloy of silicon and molybdenum, an alloy of silicon and copper, an alloy of silicon and iron, an alloy of silicon and iron and chromium, an alloy of silicon and titanium, an alloy of silicon and molybdenum and titanium, an alloy of magnesium and chromium, an alloy of magnesium and molybdenum, an alloy of magnesium and copper, an alloy of magnesium and iron, an alloy of magnesium and iron and chromium, an alloy of magnesium and titanium, an alloy of magnesium and molybdenum. In a further preferred embodiment of the method according to the invention, the metal powder composition used in step (a) comprises powdered aluminum. In a particularly preferred embodiment of the method according to the invention, the metal powder composition used in step (a) consists of powdered aluminum and one or more powdered wax components.
[0028] In a preferred embodiment, the metal powder composition used in step (a) of the method according to the invention comprises one or more wax components. The addition of the wax components increases the flowability of the metal powder composition and thus improves industrial transportability. The wax components also protect the metal powder composition from water absorption and may further reduce the extent of chemical reaction between the powdered metal and water, thus inhibiting hydrogen formation.
[0029] Preferably, the metal powder composition has a metal component content in the range of 80-99.8% by weight. Here, compositions in which the metal component particles have a particle size of 5 μm to 200 μm are preferred. Particularly preferred are compositions in which 95% of the metal component particles have a particle size of 5 μm to 75 μm. In addition to the metal components in elemental form, the composition can also contain metal components in oxidized form. The oxidized components are usually in the form of oxidizing compounds, such as, for example, oxides, hydroxides and / or carbonates. Typically, the weight fraction of the oxidized components is in the range of 0.05-10% of the total weight of the metal powder composition.
[0030] In step (b) of the method according to the invention, the coated metal object 1 is heated to the melting temperature of at least one of the wax components and then cooled to room temperature to obtain a coated metal object 2. Typically, in this step, the coated metal object 1 is heated to a temperature in the range of 90-250° C. An oven is usually used as the heat source for heating the coated metal object 1 in step (b), but in principle other heat sources can be used, for example infrared lamps. Cooling to room temperature does not have to be performed at a controlled cooling rate and is typically achieved by switching off the heat source used for heating and allowing the metal object to equilibrate to room temperature. The metal object may be surrounded during step (b) by a gas atmosphere consisting of air, oxygen or an inert protective gas, which may be at ambient, normal or slightly reduced pressure (1-300 mbar). The objective in carrying out step (b) of the method according to the invention is simply to melt and cool the wax components, and it is not intended in this step to remove organic components by pyrolysis or to induce alloy formation between the metallic components. In the context of the present invention, room temperature is understood to mean a temperature of 25°C.
[0031] In one embodiment of the invention, the coated metal object 1 is heated to the melting temperature of exactly one of the wax components and then cooled to room temperature. In another embodiment, the coated metal object 1 is heated until all wax components are melted and then cooled to room temperature. In a preferred embodiment, the coated metal object 1 is heated until at least half of the total weight of all wax components is melted and then cooled to room temperature.
[0032] In step (c) of the method according to the invention, the coated metal object 2 is heat treated to form an alloy between the metallic part of the metal object and the metal powder composition, thereby obtaining a metal object 3. The heat treatment usually involves stepwise heating of the coated metal object 2 followed by cooling to room temperature. Suitable alloying conditions for step (c) are obtained from the phase diagrams of the metal and intermetallic phases involved, for example the phase diagrams of Ni and Al. For example, the proportion of Al-rich leachable components such as NiAl3 and Ni2Al3 can be controlled. The heat treatment is carried out under inert gas or reducing conditions. Reducing conditions means the presence of a gas mixture comprising hydrogen and at least one gas which is inert under the reaction conditions, for example a gas mixture comprising 50% by volume of N2 and 50% by volume of H2 is suitable. As inert gas nitrogen is preferably used. The heating can be carried out, for example, in a conveyor furnace. Suitable heating rates are in the range of 10 to 200 K / min, preferably 20 to 180 K / min. It may be advantageous to keep the temperature constant for a period of the heat treatment so that gradual heating and / or cooling occurs. During the heat treatment, the temperature is usually first increased from room temperature to about 300-400°C, at which temperature for a period of about 2-30 minutes to remove moisture and organic components from the coating, then increased to about 650-750°C until an alloy is formed between the metallic portion of the metal object and the metal powder composition, and then the metal object is quenched by contacting it with a protective gas environment at a temperature of about 200°C.
[0033] In a further aspect, the present invention further comprises a method comprising the following step (d): treating the metal object 3 with a basic solution. The treatment of the metal object 3 with the basic solution may serve to at least partially dissolve and thus remove from the metal object the metal components of the applied metal powder composition and the alloy between the metal portion of the metal object and the metal powder composition. Typically, 30-70 wt. % of the total weight of the metal components of the applied metal powder composition and the alloy between the metal portion of the metal object and the metal powder composition is removed from the metal object by the treatment with the basic solution. As the basic solution, a basic aqueous solution of NaOH, KOH, LiOH or a mixture thereof is usually used. The temperature of the basic treatment is usually kept in the range of 25-120°C. The duration of the treatment with the basic solution is usually in the range of 5 minutes to 8 hours. When the metal components are appropriately selected, the metal object obtained as a result of the treatment with the basic solution can be used as a catalyst, as disclosed in WO2019057533.
[0034] In a preferred embodiment, the treatment of the metal object 3 with the basic solution is carried out at a temperature in the range of 20-120°C and for a duration in the range of 5 minutes to 8 hours, the basic solution being an aqueous NaOH solution having a NaOH concentration of 2-30% by weight.
[0035] In a further aspect, the present invention further comprises a coated metal object obtainable by the method according to the present invention.
[0036] In a further preferred embodiment, the present invention further relates to the following method and to the metal objects obtained thereby: The metal object used in step (a) is made of a metal selected from the group consisting of Ni, Fe, Co, Cu; In step (d), the metal object 3 is treated with a basic solution.
[0037] In a further preferred embodiment, the present invention further relates to the following method and to the metal objects obtained thereby: The metal powder composition used in step (a) comprises one or more powdered metal components selected from the group consisting of aluminium, silicon, magnesium, alloys of aluminium and chromium, alloys of aluminium and molybdenum, alloys of aluminium and copper, alloys of aluminium and iron, alloys of aluminium and iron and chromium, alloys of aluminium and titanium, alloys of aluminium and molybdenum and titanium, alloys of silicon and chromium, alloys of silicon and molybdenum, alloys of silicon and copper, alloys of silicon and iron, alloys of silicon and iron and chromium, alloys of silicon and titanium, alloys of silicon and molybdenum and titanium, alloys of magnesium and chromium, alloys of magnesium and molybdenum, alloys of magnesium and copper, alloys of magnesium and iron, alloys of magnesium and iron and chromium, alloys of magnesium and titanium, alloys of magnesium and molybdenum, In step (d), the metal object 3 is treated with a basic solution.
[0038] In a further preferred embodiment, the present invention further relates to the following method and to the metal objects obtained thereby: The metal object used in step (a) is made of a metal selected from the group consisting of Ni, Fe, Co, Cu; The metal powder composition used in step (a) comprises one or more powdered metal components selected from the group consisting of aluminium, silicon, magnesium, alloys of aluminium and chromium, alloys of aluminium and molybdenum, alloys of aluminium and copper, alloys of aluminium and iron, alloys of aluminium and iron and chromium, alloys of aluminium and titanium, alloys of aluminium and molybdenum and titanium, alloys of silicon and chromium, alloys of silicon and molybdenum, alloys of silicon and copper, alloys of silicon and iron, alloys of silicon and iron and chromium, alloys of silicon and titanium, alloys of silicon and molybdenum and titanium, alloys of magnesium and chromium, alloys of magnesium and molybdenum, alloys of magnesium and copper, alloys of magnesium and iron, alloys of magnesium and iron and chromium, alloys of magnesium and titanium, alloys of magnesium and molybdenum and titanium.
[0039] In a further preferred embodiment, the present invention further relates to the following method and to the metal objects obtained thereby: The metal object used in step (a) is made of a metal selected from the group consisting of Ni, Fe, Co, Cu; The metal powder composition used in step (a) comprises one or more powdered metal components selected from the group consisting of aluminium, silicon, magnesium, alloys of aluminium and chromium, alloys of aluminium and molybdenum, alloys of aluminium and copper, alloys of aluminium and iron, alloys of aluminium and iron and chromium, alloys of aluminium and titanium, alloys of aluminium and molybdenum and titanium, alloys of silicon and chromium, alloys of silicon and molybdenum, alloys of silicon and copper, alloys of silicon and iron, alloys of silicon and iron and chromium, alloys of silicon and titanium, alloys of silicon and molybdenum and titanium, alloys of magnesium and chromium, alloys of magnesium and molybdenum, alloys of magnesium and copper, alloys of magnesium and iron, alloys of magnesium and iron and chromium, alloys of magnesium and titanium, alloys of magnesium and molybdenum, In step (d), the metal object 3 is treated with a basic solution.
[0040] In a further preferred embodiment, the present invention further relates to the following method and to the metal objects obtained thereby: The metal object used in step (a) is made of a metal selected from the group consisting of Ni, Fe, Co, Cu; The metal powder composition used in step (a) comprises one or more powdered metal components selected from the group consisting of aluminium, silicon, magnesium, alloys of aluminium and chromium, alloys of aluminium and molybdenum, alloys of aluminium and copper, alloys of aluminium and iron, alloys of aluminium and iron and chromium, alloys of aluminium and titanium, alloys of aluminium and molybdenum and titanium, alloys of silicon and chromium, alloys of silicon and molybdenum, alloys of silicon and copper, alloys of silicon and iron, alloys of silicon and iron and chromium, alloys of silicon and titanium, alloys of silicon and molybdenum and titanium, alloys of magnesium and chromium, alloys of magnesium and molybdenum, alloys of magnesium and copper, alloys of magnesium and iron, alloys of magnesium and iron and chromium, alloys of magnesium and titanium, alloys of magnesium and molybdenum, One or more wax components are added to the metal powder composition.
[0041] In a further preferred embodiment, the present invention further relates to the following method and to the metal objects obtained thereby: The metal object used in step (a) is made of a metal selected from the group consisting of Ni, Fe, Co, Cu; The metal powder composition used in step (a) comprises one or more powdered metal components selected from the group consisting of aluminium, silicon, magnesium, alloys of aluminium and chromium, alloys of aluminium and molybdenum, alloys of aluminium and copper, alloys of aluminium and iron, alloys of aluminium and iron and chromium, alloys of aluminium and titanium, alloys of aluminium and molybdenum and titanium, alloys of silicon and chromium, alloys of silicon and molybdenum, alloys of silicon and copper, alloys of silicon and iron, alloys of silicon and iron and chromium, alloys of silicon and titanium, alloys of silicon and molybdenum and titanium, alloys of magnesium and chromium, alloys of magnesium and molybdenum, alloys of magnesium and copper, alloys of magnesium and iron, alloys of magnesium and iron and chromium, alloys of magnesium and titanium, alloys of magnesium and molybdenum, adding one or more wax components to the metal powder composition; In step (d), the metal object 3 is treated with a basic solution.
[0042] In a further preferred embodiment, the present invention further relates to the following method and to the metal objects obtained thereby: The metal object used in step (a) is made of a metal selected from the group consisting of Ni, Fe, Co, Cu; The metal powder composition used in step (a) comprises one or more powdered metal components selected from the group consisting of aluminium, silicon, magnesium, alloys of aluminium and chromium, alloys of aluminium and molybdenum, alloys of aluminium and copper, alloys of aluminium and iron, alloys of aluminium and iron and chromium, alloys of aluminium and titanium, alloys of aluminium and molybdenum and titanium, alloys of silicon and chromium, alloys of silicon and molybdenum, alloys of silicon and copper, alloys of silicon and iron, alloys of silicon and iron and chromium, alloys of silicon and titanium, alloys of silicon and molybdenum and titanium, alloys of magnesium and chromium, alloys of magnesium and molybdenum, alloys of magnesium and copper, alloys of magnesium and iron, alloys of magnesium and iron and chromium, alloys of magnesium and titanium, alloys of magnesium and molybdenum, adding one or more wax components to the metal powder composition; The metal object used in step (a) is a metal foam.
[0043] In a further preferred embodiment, the present invention further relates to the following method and to the metal objects obtained thereby: The metal object used in step (a) is made of a metal selected from the group consisting of Ni, Fe, Co, Cu; The metal powder composition used in step (a) comprises one or more powdered metal components selected from the group consisting of aluminium, silicon, magnesium, alloys of aluminium and chromium, alloys of aluminium and molybdenum, alloys of aluminium and copper, alloys of aluminium and iron, alloys of aluminium and iron and chromium, alloys of aluminium and titanium, alloys of aluminium and molybdenum and titanium, alloys of silicon and chromium, alloys of silicon and molybdenum, alloys of silicon and copper, alloys of silicon and iron, alloys of silicon and iron and chromium, alloys of silicon and titanium, alloys of silicon and molybdenum and titanium, alloys of magnesium and chromium, alloys of magnesium and molybdenum, alloys of magnesium and copper, alloys of magnesium and iron, alloys of magnesium and iron and chromium, alloys of magnesium and titanium, alloys of magnesium and molybdenum, adding one or more wax components to the metal powder composition; In step (d), the metal object 3 is treated with a basic solution, The metal object used in step (a) is a metal foam. [Brief description of the drawings]
[0044] [Figure 1] FIG. 1 shows a flat blank made of wire mesh. [Diagram 2] FIG. 1 shows the optical transparency of a flat blank made of cobalt foam. [Diagram 3] FIG. 1 shows the optical transparency of a flat blank made of cobalt foam. [Figure 4] FIG. 1 shows an SEM image of a nickel / cobalt foam sample. [Diagram 5] FIG. 1 shows a flat blank made of nickel foam.
[0045] Working Example A - Nickel Foam Coating 1. Application of the metal powder composition to the metal object Weight per unit area: 1000g / m 2First, 40 g of binder solution (2.5 wt % polyethyleneimine aqueous solution) was sprayed onto two flat nickel metal foams (1.9 mm × 300 mm × 860 mm) with an average pore size of 580 μm. Immediately afterwards, dried powdered aluminum (particle size d 99 = 90 μm) mixed with 3 wt. % of powdered Ceretan®-7080 wax (melting point in the range of 140-160°C) was applied to the metal object (approximately 400 g / m 2 ).
[0046] 2. Melting and re-solidification of wax components One of the metal foams was then heated to 160°C in a laboratory oven and then cooled to room temperature again.
[0047] 3. Alloy formation by heat treatment Both metal foams were then subjected to alloying by heat treatment in a conveyor sintering furnace (manufacturer: Sarnes) under nitrogen atmosphere by heating the furnace from room temperature to 725 °C over 15 min, holding the temperature at 725 °C for 2 min, and then quenching by contacting with a nitrogen atmosphere at 200 °C.
[0048] 4. Evaluation of uniformity of alloy coating Finally, to obtain information on the uniformity of the alloy coating of both metal foams, the variation in weight per unit area of the subregions of both metal foams was investigated by punching out 36 circular cutouts with a diameter of 30 mm from every subregion of both metal foams and weighing them.
[0049] Next, the PFR value (powder foam ratio) was calculated as follows: PFR = 100 x (m [after sintering] - m [initial foam]) / m [after sintering] Where: m [after sintering] is the weight of each 30 mm diameter circular cutout punched out after alloy formation, m[initial foam] is the weight of the 30 mm diameter circular cutout of the metal foam before the experiment began.
[0050] Finally, the mean and experimental standard deviation for each series of PFR values were determined for both metal foams.
[0051] For metal foams that underwent the wax melting and resolidification steps, the following results were obtained: Average: 29.7 Standard deviation: 0.5
[0052] For metal foams that did not undergo the wax melting and resolidification steps, the following results were obtained: Average: 27.7 Standard deviation: 2.3
[0053] The results clearly show that by adding wax and carrying out the steps of melting and recooling before alloy formation by heat treatment, a significant improvement in the uniformity of the alloy coating is achieved in the metal object according to the invention.
[0054] B - Wire mesh coating 1. Application of the metal powder composition to the metal object Two metal objects made of commercially available flat nickel wire mesh (mesh size 0.163 mm) were first sprayed with a binder solution (a 2.5 wt % polyethyleneimine solution in water). Immediately afterwards, both metal objects were sprayed with dry powdered aluminum (particle size d 99 = 90 μm) was applied with the same amount of a mixture of 3 wt % powdered Ceretan®-7080 wax (melting point in the range of 140-160° C.).
[0055] 2. Melting and re-solidification of wax components One of the metal objects was then heated to 160°C in a laboratory oven and then cooled to room temperature again, while the other metal object was dried in air at room temperature for 24 hours.
[0056] The translucency of both metal objects was then examined by illuminating one side with a bright lamp. The results showed that the metal object that had undergone the wax melting and resolidification steps had a much more uniform translucency than the object that had been dried at room temperature in air. This indicates that the applied powder was more uniformly distributed on the metal object that had been actively dried at 160°C.
[0057] 3. Alloy formation by heat treatment Both metal objects were then subjected to alloying by heat treatment in an industrial belt sintering furnace under nitrogen atmosphere by heating the oven from room temperature to 725°C over 15 minutes, holding the temperature at 725°C for 2 minutes, and then quenching by contacting with a nitrogen atmosphere at 200°C.
[0058] C - Cobalt Foam Coating 1. Application of the metal powder composition to the metal object Weight per unit area: 1000g / m 2 First, 40 g of binder solution (2.5 wt% polyethyleneimine aqueous solution) was sprayed onto two flat cobalt metal foams (1.9 mm × 300 mm × 860 mm) with an average pore size of 580 μm. Immediately afterwards, Al / Cr dry powder (containing 5 wt% Cr) (particle size d 90 <63μm, d 50 = 35 μm) mixed with 3 wt. % of powdered Ceretan®-7080 wax (melting point range 140-160°C) was applied to the metal object (approximately 400 g / m 2 ).
[0059] 2. Melting and re-solidification of wax components One of the metal objects was then heated to 160°C in a laboratory oven and then cooled to room temperature again, while the other metal object was dried in air at room temperature for 24 hours.
[0060] Afterwards, the translucency of both metal objects was examined by illuminating one side with a bright lamp. The results showed that the metal object that had undergone the wax melting and resolidification steps had a much more uniform translucency than the object that had been dried at room temperature in air. This suggests that the distribution of the applied powder was less uniform in the object that had been dried at room temperature in air. This result could be confirmed by SEM images, where it was possible to identify closed pores and localized overloading of the object.
[0061] 3. Alloy formation by heat treatment Both metal objects were then subjected to alloying by heat treatment in a belt sintering furnace (manufacturer: Sarnes) under a nitrogen atmosphere, where the furnace was heated from room temperature to 700 °C in 15 minutes, the temperature was kept at 700 °C for 2 minutes, and then quenched by contacting with a nitrogen atmosphere at 200 °C.
[0062] 4. Evaluation of uniformity of alloy coating Finally, to obtain information on the uniformity of the alloy coating of both metal objects, the variation in weight per unit area of the regions of both metal objects was investigated. For this purpose, 36 circular cutouts with a diameter of 30 mm were punched out from all the regions of both metal foams and weighed.
[0063] The PFR value was then determined from: PFR = 100 x (m [after sintering] - m [initial material]) / m [after sintering] Where: m [after sintering] is the weight of each 30 mm diameter circular cutout punched out after alloy formation, m[initial object] is the weight of the 30 mm diameter circular cutout of the metal foam before the experiment began.
[0064] Finally, the mean and experimental standard deviation of each series of PFR values were determined for both metal objects.
[0065] For metal objects that underwent the wax melting and resolidification steps, the following results were obtained: Average: 28.2 Standard deviation: 0.7
[0066] For metal objects that did not undergo the wax melting and resolidification steps, the following results were obtained: Average: 26.8 Standard deviation: 2.7
[0067] This result demonstrates once again that by adding wax and carrying out the steps of melting and recooling prior to alloy formation by heat treatment, a significant improvement in the uniformity of the alloy coating is achieved in the metal object according to the invention.
[0068] D - Nickel / Cobalt Foam Coating 1. Application of the metal powder composition to the metal object Weight per unit area: 1000g / m 2 Two flat-shaped nickel / cobalt (42 wt% nickel, 58 wt% cobalt, produced by template-assisted layer-by-layer electroplating) metal foams (1.9 mm × 300 mm × 860 mm) with an average pore size of 580 μm were first sprayed with 40 g of binder solution (2.5 wt% polyethyleneimine aqueous solution). Immediately afterwards, Al / Cr dry powder (containing 5 wt% Cr) (particle size d 90 <63μm, d 50 = 35 μm) mixed with 3 wt. % of powdered Ceretan®-7080 wax (melting point range 140-160°C) was applied to the metal object (approximately 400 g / m 2 ).
[0069] 2. Melting and re-solidification of wax components One of the metal objects was then heated to 160°C in a laboratory oven and then cooled to room temperature again, while the other metal object was dried in air at room temperature for 24 hours.
[0070] Afterwards, the translucency of both metal objects was examined by illuminating one side with a bright lamp. The results showed that the metal object that had undergone the wax melting and resolidification steps had a much more uniform translucency than the object that had been dried at room temperature in air. This suggests that the distribution of the applied powder was less uniform in the object that had been dried at room temperature in air. This result could be confirmed by SEM images, where it was possible to identify closed pores and localized overloading of the object.
[0071] 3. Alloy formation by heat treatment Both metal objects were then subjected to alloying by heat treatment in a belt sintering furnace (manufacturer: Sarnes) under a nitrogen atmosphere, where the furnace was heated from room temperature to 700 °C in 15 minutes, the temperature was kept at 700 °C for 2 minutes, and then quenched by contacting with a nitrogen atmosphere at 200 °C.
[0072] 4. Evaluation of uniformity of alloy coating Finally, to obtain information on the uniformity of the alloy coating of both metal objects, the variation in weight per unit area of the regions of both metal objects was investigated. For this purpose, 36 circular cutouts with a diameter of 30 mm were punched out from all the regions of both metal foams and weighed.
[0073] The PFR value was then determined from: PFR = 100 x (m [after sintering] - m [initial material]) / m [after sintering] Where: m [after sintering] is the weight of each 30 mm diameter circular cutout punched out after alloy formation, m[initial object] is the weight of the 30 mm diameter circular cutout of the metal foam before the experiment began.
[0074] Finally, the mean and experimental standard deviation of each series of PFR values were determined for both metal objects.
[0075] For metal objects that underwent the wax melting and resolidification steps, the following results were obtained: Average: 28.4 Standard deviation: 0.6
[0076] For metal objects that did not undergo the wax melting and resolidification steps, the following results were obtained: Average: 27.1 Standard deviation: 2.4
[0077] This result demonstrates once again that by adding wax and carrying out the steps of melting and recooling prior to alloy formation by heat treatment, a significant improvement in the uniformity of the alloy coating is achieved in the metal object according to the invention.
[0078] E - Nickel Foam Drop Test 1. Application of the metal powder composition to the metal object Weight per unit area: 1000g / m 2 First, 40 g of binder solution (2.5 wt % polyethyleneimine aqueous solution) was sprayed onto a flat plate of nickel metal foam (1.9 mm × 300 mm × 860 mm) with an average pore size of 580 μm. Immediately afterwards, dried powdered aluminum (particle size d 99 = 90 μm) mixed with 3 wt. % of powdered Ceretan®-7080 wax (melting point in the range of 140-160°C) was applied to the metal object (approximately 400 g / m 2 ).
[0079] 2. Melting and re-solidification of wax components The metal object was then cut into pieces with dimensions of 1.9 x 300 x 200 mm. One was heated to 160°C in a laboratory oven and then cooled to room temperature again. The other metal object was dried in air at room temperature for 24 hours. The weight of the metal object with dimensions of 1.9 x 300 x 200 mm is approximately 85 g. This weight is composed of 23 g of powder, less than 1 g of wax, and approximately 61 g of Ni foam.
[0080] Afterwards, the translucency of both metal objects was examined by illuminating one side with a bright lamp. The results showed that the metal object that had undergone the wax melting and resolidification steps had a much more uniform translucency than the object that had been dried at room temperature in air. This suggests that the distribution of the applied powder was less uniform in the object that had been dried at room temperature in air. This result could be confirmed by SEM images, where it was possible to identify closed pores and localized overloading of the object.
[0081] 3. Drop test Both metal objects were then weighed and dropped onto a table from a height of 10 cm. Finally, the metal objects were weighed again.
[0082] The results showed that metal objects that were dried in air at room temperature for 24 hours lost approximately 6% of the weight of the applied metal powder composition when dropped onto a table, whereas metal objects that underwent melting and resolidification steps lost less than 1% of the weight of the applied metal powder composition.
[0083] Description of the drawings Figure 1 The figure shows a flat blank made of wire mesh: on the right, in its original, i.e. uncoated form, and on the left, in its coated form, i.e. after first applying the aluminum powder composition and then carrying out a melting and resolidification cycle of the wax component, as described in Example B, but without subsequent alloying by heat treatment.
[0084] Figure 2 This figure shows the translucency of a flat blank of cobalt foam as used in Example C, first applied with the metal powder composition as described in Example C, then dried in air at room temperature for 24 hours, illuminated on one side with a bright lamp. However, this metal powder composition was not subsequently alloyed by heat treatment. It can be seen that the distribution of translucency is less uniform than in Figure 3. The non-translucent areas indicate local overloading of the metal powder composition due to closed pores, thus suggesting a non-uniform distribution of the applied metal powder composition.
[0085] Figure 3 This figure shows the translucency of a flat blank of cobalt foam that was first applied with the metal powder composition and then cycled through melting and resolidifying the wax component as described in Example C, when illuminated on one side with a bright lamp. However, this metal powder composition was not subsequently alloyed by heat treatment. Compared to Figure 2, the distribution of translucency is much more uniform, suggesting a more uniform distribution of the applied metal powder composition.
[0086] Figure 4 This figure shows scanning electron microscope (SEM) images of nickel / cobalt foam samples in coated form, i.e., samples that have been applied with the metal powder composition as described in Example D, but have not been subsequently alloyed by heat treatment. The sample on the left was applied with the metal powder composition, then dried at room temperature in air for 24 hours, and then examined under SEM. The sample on the right was applied with the metal powder composition, then subjected to a melting and resolidification cycle of the wax component, and then examined under SEM. Closed pores and partially uncoated metal web are clearly visible in the sample on the left. The sample on the right shows a uniform coating of the metal web, without closed pores.
[0087] Figure 5 On the left side of the figure, a flat blank made of nickel foam is shown. The blank was first coated with an aluminum powder composition as described in Example E and then dried in air at room temperature for 24 hours. The metal powder composition was not subsequently alloyed by heat treatment. On the right side of the figure, the powder residue remaining after the powder-coated foam was put down and picked up again is shown.
Claims
1. 1. A method for producing a coated metal object, the method comprising the steps of: (a) obtaining a coated metal object 1 by applying a metal powder composition to the metal object, the coating comprising one or more wax components; (b) heating the coated metal object 1 to the melting temperature of at least one of the wax components and then cooling to room temperature to obtain a coated metal object 2; (c) heat treating the coated metal object 2 to form an alloy between the metal portion of the metal object and the metal powder composition, thereby obtaining a metal object 3; where The metal object used in step (a) comprises a metal component selected from the group consisting of nickel, cobalt, copper and iron; The metal powder composition used in step (a) comprises a powdered metal component comprising aluminium, silicon or magnesium, either in elemental or alloyed form; The metal object used in step (a) is in the form of a foam, a mesh, a woven fabric, a weft knit or a warp knit; method.
2. The method of claim 1 , wherein the metal object used in step (a) is a metal foam.
3. The metal object used in step (a) is: (i) Nickel metal (ii) Cobalt metal (iii) Metallic copper (iv) Nickel and cobalt alloys (v) Nickel and copper alloys (vi) An assembly of two overlapping layers of two separate metal components, one of said metal components forming an inner layer of said metal object and the other of said metal components forming an outer layer of said metal object, said metal components being selected from the list of the following combinations: nickel on the inner side and cobalt on the outer side, iron on the inner side and nickel on the outer side.
3. The method according to claim 1 or 2, comprising any one of the steps:
4. The method according to any one of claims 1 to 3, wherein the metal object used in step (a) is made of a metal selected from the group of Ni, Fe, Co, Cu.
5. 5. The method of any one of claims 1 to 4, wherein the metal powder composition used in step (a) of the method comprises one or more powdered metal components selected from the group consisting of aluminium, silicon, magnesium, alloys of aluminium and chromium, alloys of aluminium and molybdenum, alloys of aluminium and copper, alloys of aluminium and iron, alloys of aluminium and iron and chromium, alloys of aluminium and titanium, alloys of aluminium and molybdenum and titanium, alloys of silicon and chromium, alloys of silicon and molybdenum, alloys of silicon and copper, alloys of silicon and iron, alloys of silicon and iron and chromium, alloys of silicon and titanium, alloys of silicon and molybdenum and titanium, alloys of magnesium and chromium, alloys of magnesium and molybdenum, alloys of magnesium and copper, alloys of magnesium and iron, alloys of magnesium and iron and chromium, alloys of magnesium and titanium, alloys of magnesium and molybdenum and titanium.
6. 6. The method of claim 1, wherein the metal powder composition used in step (a) comprises powdered aluminum and one or more powdered wax components.
7. 7. The method according to claim 1, wherein at least one of the wax components in the coating of the coated metal object 1 obtained in step (a) has a solidification temperature in the range of 45 to 160°C.
8. The method of any one of claims 1 to 7, wherein one or more wax components are added to the metal powder composition used in step (a).
9. (d) treating said metal object 3 with a basic solution; The method of any one of claims 1 to 8, further comprising:
10. 10. The method of claim 9, wherein the treatment of the metal object 3 with the basic solution is carried out at a temperature in the range of 20-120° C. and for a duration in the range of 5 minutes to 8 hours, the basic solution being an aqueous NaOH solution having a NaOH concentration of 2-30% by weight.
Citation Information
Patent Citations
Surface modified metal foam, method of making same, and use thereof
JP2016513173A
Method for producing molded catalyst body
JP2020534150A
Method for producing a shaped catalyst body
WO2019057533A1